ANALISIS PENGENDALIAN PERSEDIAAN PAKAN TERNAK PADA CV SINAR TONGLO - Septika Kadang; Muh. Sabir (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2024)
This research aims to determine the optimal amount of inventory when placing a reorder, to find out when is the right time to reorder merchandise at CV. Tonglo Rays. The method used is a descriptive method. This analysis was carried out by collecting data from CV. Sinar Tonglo, then manages the data that has been collected using Economic Order Quantity (EOQ) and Reorder Point (ROP) calculations. The results of this research show that the number of orders was 4,539,398, the time required was 20 days, the safety stock was 124,380 kg, and reorders were from CV. Sinar Tonglo what must be done is when the remaining merchandise inventory is 346,772 kg